2007
DOI: 10.1186/1471-2229-7-61
|View full text |Cite
|
Sign up to set email alerts
|

UV-B-induced signaling events leading to enhanced-production of catharanthine in Catharanthus roseus cell suspension cultures

Abstract: BackgroundElicitations are considered to be an important strategy towards improved in vitro production of secondary metabolites. In cell cultures, biotic and abiotic elicitors have effectively stimulated the production of plant secondary metabolites. However, molecular basis of elicitor-signaling cascades leading to increased production of secondary metabolites of plant cell is largely unknown. Exposure of Catharanthus roseus cell suspension culture to low dose of UV-B irradiation was found to increase the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 59 publications
8
58
0
Order By: Relevance
“…STR is identified as VIN-biosynthetic gene and one of the bottlenecks involved in the biosynthesis of TIAs (Pandey et al 2016). The expression of TDC and STR affected the accumulation of CAT content (Ramani & Chelliah 2007). In addition, DAT is the key enzyme catalyzing the last step of the reaction of the biosynthesis of VIN from tabersonine (Magnotta et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…STR is identified as VIN-biosynthetic gene and one of the bottlenecks involved in the biosynthesis of TIAs (Pandey et al 2016). The expression of TDC and STR affected the accumulation of CAT content (Ramani & Chelliah 2007). In addition, DAT is the key enzyme catalyzing the last step of the reaction of the biosynthesis of VIN from tabersonine (Magnotta et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that MAPK played important roles in UV-B signaling-induced accumulation of catharanthine (Ramani and Chelliah 2006). However, little is known about whether MAPK is involved in phenylpropanoid pathway isoflavone production in the soybean sprouts under UV-B radiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, MAPK play significant roles in UV-B signaling leading to stimulation of tryptophan decarboxylase (Tdc) and strictosidine synthase (Str) genes and the accumulation of catharanthine in C. roseus cell suspension cultures (Ramani and Chelliah 2006), implying that the MAPK signal pathway(s) was related to secondary metabolism. Both of MAPK and isoflavones accumulation are the results of stress stimuli.…”
mentioning
confidence: 99%
“…1 Many of the MIAs and transcripts of genes involved in MIAs biosynthesis show enhanced accumulation in response to stresses such as UV and plant stress hormone methyl jasmonate (MeJA). [2][3][4][5][6][7] Mitogen-activated protein kinase (MAPK) signaling is an evolutionarily conserved mechanism in eukaryotes and involved in transducing extracellular signals to produce responses to the stress in question. 8 In C. roseus involvement of protein phosphorylation as well as MAP kinase in stress-induced transcripts accumulation of key genes of MIA biosynthesis have been speculated.…”
mentioning
confidence: 99%
“…8 In C. roseus involvement of protein phosphorylation as well as MAP kinase in stress-induced transcripts accumulation of key genes of MIA biosynthesis have been speculated. 7,9 Recently, we have shown cloning and characterization of CrMPK3, a MAPK from C. roseus. CrMPK3 showed enhanced transcripts accumulation and MAPK activity in response to wounding, UV treatment and MeJA application in C. roseus.…”
mentioning
confidence: 99%